Pengaruh Perbandingan Ikan Patin (Pangasius sp.) dan Ayam Terhadap Tingkat Kesukaan Galantin - Rahmadewi, Yunda Maymanah; Rizkia, Emi Fajar; Pangastuti, Palupi Melati (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 7 No 2 (2022), 2022)
The purpose of this study was to determine the level of preference for galantine from a mixture of catfish ( Pangasius sp .) and chicken which was assessed from the level of preference for the sensory attributes of color, aroma, texture, taste, and overall preference. This study used a completely randomized design (CRD). Part of the substitution of raw materials for animal protein sources in this study was catfish fillet with 3 levels, namely 604 (100% catfish fillet: 0% chicken fillet), 581 (50% catfish fillet: 50% chicken fillet), and 738. (0% fillet of catfish: 100% chicken fillet) which was then tested for preference for color, aroma, taste, texture, and overall preference. The use of catfish as a substitute for chicken meat in galantin products has a significant difference in the average level of preference for color, aroma, taste, and overall but not significantly different in the average level of preference for texture.